STUDI PENERAPAN HACCP (HAZARD ANALYSIS CRITICAL CONTROL POINT) PADA PROSES PENGOLAHAN MI SAGU - Miskiyah Miskiyah; Widaningrum Widaningrum; Hetty Herawati (Badan Standardisasi Nasional, 2006)
Sago is one of local food at some regions in Indonesia. Processing technology of sago become noodle is one way to vary sago processing product. The main factor that effect sago noodle processing are quality, self life, andlimited marketing of sago noodle. Thus to make sago noodle assurance, HACCP plan is needed. This study purposes to assess the HACCP system guidelines which are suitable for processing of sago noodle base on 7 principles system guidelines. Result of the study shown that sago noodle processing have chemical hazard (heavy metal contamination, coloring and textures), and microbiological hazard (pathogens from operator such as Streptococcus; also water source such as Coliform and Shigella). As conclusion, HACCP system guidelines on sago noodle processing is very important to develop quality and safety assurance.